Effectiveness of Fun Learning Method in Learning to Read and Write the Qur'an (BTQ) - Surya Permadi, M.Syafrany; Nadlif, Ainun (Institut Agama Islam An-Nawawi Purworejo, 2024)
Learning to read and write the Qur'an (BTQ) at SMP Negeri 2 Sukodono is included in intracurricular learning. The complex BTQ learning material requires an innovative learning method to overcome students' boredom with conventional methods used by teachers. The application of fun learning method in BTQ learning is considered effective enough to overcome students' boredom. It can be seen in the learning process that students are more active in asking questions, students' understanding of the material increases, this is known through the lighter questions given by the teacher to students during pre and post-learning. This research method uses descriptive qualitative methods, with data collection techniques, namely observation, interviews, and documentation. While data analysis techniques use data reduction techniques, data presentation and conclusion drawing. This study aims to determine the effectiveness of the fun learning method in BTQ learning at SMP Negeri 2 Sukodono. The results of this study indicate that the application of fun learning method in BTQ learning at SMP Negeri 2 Sukodono is considered effective to continue to be used. This is proven by the achievement of learning effectiveness indicators including the systematic management of learning implementation, and the establishment of a good communication process between students and teachers.